Correlation Analysis of Emotional Intelligence and Mathematical Literacy of Junior High School Students on Pythagoras Theorem Material - Nurhabibah; Siti Apiya; Fadillah Hakim Assegaf; Surya Amami Pramuditya, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Mathematical literacy refers to an individual’s ability for formulating, applying, and interpreting in diverse contexts. This encompassed mathematical reasoning as well as the practical application of mathematical concepts, procedures, facts, and tools to clarify phenomena related to emotional intelligence. The research was conducted at SMPN 2 Suranenggala with 3 samples of grade VIII students. The effective emotional control fosters a more comfortable learning environment, improving students’ understanding of mathematical materials. Establishing a connection between emotional intelligence and mathematical comprehension are essential for assessing students’ abilities to grasp mathematical concepts represented by symbols, numbers, and complex operations. This study employs Emotional Quotient indicators, as outlined by Daniel Goleman, which includes self-awareness, self regulations, self-motivations, empathys, and social skills. Students with high emotional intelligence tend to manage stress and anxiety more effectively when tackling math tasks, enabling them to address problems related to the Pythagorean Theorem easily. As a result, learning strategies can greatly improve students' mathematical competencies. The indicators of emotional intelligence such as recognizing one’s emotions, practicing self-management, and demonstrating social awareness are crucial in this process. Students with having heightened sense of emotional intelligence is better than equipped to cope with the stress and anxiety that may arise during mathematical tasks, allowing them to approach Pythagorean Theorem problems in a more focused and efficient manner.